Does sports therapy affect momentary affective states? Feasibility of intensive longitudinal case studies in forensic psychiatry - Reimer, Vanessa; Kanning, Martina K. (Frontiers in Psychiatry, 2023)
Physical exercise interventions improve quality of life in people with mental disorders and improve abstinence and cravings in substance use disorders patients in both the short and long term. In people with mental illness, physical exercise interventions significantly reduce psychiatric symptoms of schizophrenia and symptoms of anxiety. For forensic psychiatry, there is little empirical evidence supporting mental health-enhancing effects of physical exercise interventions. Interventional studies in forensic psychiatry deal mainly with three problems: heterogeneity of the individuals, a small sample size and a low compliance rate. Intensive longitudinal case studies could be a suitable approach to address these methodological challenges in forensic psychiatry. This study uses an intensive longitudinal design to determine whether forensic psychiatric patients are content to complete several data assessments per day over the course of several weeks. The feasibility of this approach is operationalized by the compliance rate. Additionally, single case studies examine the effects of sports therapy (ST) on momentary affective states (energetic arousal, valence, calmness). The results of these case studies reveal one aspect of feasibility and offer insights into the effects of forensic psychiatric ST on the affective states among patients with different conditions. The patients' momentary affective states were recorded before (PRE), after (POST) and one hour after (FoUp1h) ST by questionnaires. Ten individuals (Mage = 31.7, SD = 11.94; 60% male) participated in the study. A total of 130 questionnaires were completed. To perform the single case studies, data of three patients were considered. Repeated-measures ANOVA was performed for the individual affective states to test for main effects of ST. Due to the results, ST has no significant effect on none of the three affect dimensions. However, effect sizes varied between small to medium (energetic arousal: η2 = 0.01, η2 = 0.07, η2 = 0.06; valence: η2 = 0.07; calmness: η2 = 0.02) in the three patients. Intensive longitudinal case studies are a possible approach to address heterogeneity and the low sample size. The low compliance rate in this study reveals that the study design needs to be optimized for future studies.